The Optimization of Complete Systematic Land Registration (PTSL) - Puspita S., Annesya; Prayitno, Ahmad Hadi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The right to own land is a very important right, this is a guarantee of legal certainty regarding land ownership. In order to achieve optimization in land registration, the government created a complete systematic land registration system or PTSL. In fact, the implementation of PTSL has not been optimal, especially in Pati Regency. Based on the results of the research conducted, it can be understood that the implementation of PTSL in Pati Regency has not been able to materialize effectively. There are strict sanctions from the government.Keywords: Complete; Land; Registration; Systematic.